Impact of awareness, readiness, control, response, and technology usage on crisis management of drones threats in Dubai International Airport - Al Jasmi, Mohamad Ibrahim Hassan Mohamad (2022)
Drones offer many advantages but also present risks to sensitive areas like airports. The present study investigates the significant relationship between crisis readiness, crisis awareness, crisis control, and crisis response to crisis management. Specifically, this study examines the interaction of technology usage in the Dubai international airport in the conditions of drone threats. The target population selected for this research equates to the number of both senior and junior staff working at the Dubai international airport. There are thousands of staff working in the various airport operations but no official numbers have been made public. The data for this study came from 364 respondents, and it was gathered through questionnaires that were collected in person. The technique of sample selection is based on convenience. The results show that there is a 63.1% variance in crisis management that can be explained by the four independent factors. The finding further revealed that the ability to respond to a crisis has the best predictive power (Beta = 0.368), followed by crisis awareness (Beta = 0.319), crisis preparedness (Beta = 0.289), and crisis control (Beta = 0.107). The relationship between crisis readiness and moderating influence is not significant, however the other three variables have significant moderating influences. These findings are significant because they assess the Impact of Crisis readiness on Crisis Management, Crisis Awareness and Crisis Control of Drones’ Threats at DIA. The study recommends an investigation into the awareness and readiness in managing drone crises at the UAE Airport to improve effectiveness and also performance of the organization and also speed in responding to growth.